To Propose a Checklist for Railway Temporary Station Criteria of Gemas-Johor Bharu Electrified Double Track Project - Rosdan, Rabiatul Adawiyah; Abd Latif, Muhamad Faiz; Ramli, Mimi Faisyalini (Progress in Engineering Application and Technology, 2022)
As for now, there is no specific standard requirement for the railway temporary station. Without the specific standard requirement and criteria for railway temporary station, the acceptance process might take longer time due to sudden issues raise during the inspection and migration acceptance process. The purpose of the study was to identify and design a checklist for railway temporary station, and to develop a general railway temporary station layout. The study adopted the Content Validity Index (CVI) research design which was premised on the content validation of each items listed and expert panels approach. The development of the CVI were examined using the universal acceptable values of content validity index. The cut off for CVI is ≥ 0.78. As results, a total of 52 items of the temporary station criteria was design and 43 out of 52 items was validated and achieved the acceptable CVI values of ≥ 0.78. Finally, at the end of the content validity study, the 43 items of the checklist and a layout of general temporary station criteria was developed for a better implementation in the future.